ANALYSIS OF MARINE ECOTOURISMDEVELOPMENT IN MANGROVE FORESTS TO IMPROVE THE WELFARE OF THE LUBUK KERTANG VILLAGE COMMUNITY LANGKAT REGENCY - Wahyu Zuliah Sasmita; Rusiadi, Rusiadi; Annisa Ilmi Faried (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2024)
The long distance traveled and the lack of infrastructure such as roads and public transportation have reduced the interest of tourists to visit the Mangrove Forest Marine Tourism object. The lack of resting places for tourists such as cottages and lodging places also triggers the lack of interest of tourists to visit. Conversely, if the availability of infrastructure such as good roads and easy to pass, signposts, and the availability of comfortable and quiet resting places can be the main attraction for tourists who want to visit these attractions. This study aims to determine whether the value of natural beauty, educational value, facilities and infrastructure, tourists, promotions, fees, handicrafts, and income are relevant to improving the welfare of the community in Lubuk Kertang Village, Langkat Regency and to determine the role of the government in developing ecotourism attractiveness in improve the welfare of the community in Lubuk Kertang Village, Langkat Regency. What is examined is whether the value of natural beauty, educational value, facilities and infrastructure, tourists, promotions, fees, handicrafts, and income are relevant to improving the welfare of the community in Lubuk Kertang Village, Langkat Regency and what is the role of the government in developing ecotourism attractiveness in improving people's welfare. in Lubuk Kertang Village, Langkat Regency. With a sample of 207 respondents, which were collected by distributing questionnaires and processing data using Confirmatory factor analysis (CFA) and Multiple Linear Regression. Based on the results of the Confirmatory Factor Analysis (CFA) test in the KMO and Bartlett's test table, it shows that promotion, tourists, educational values and income significantly affect the welfare of the people in Lubuk Kertang Village, while the value of natural beauty, infrastructure, user fees and handicrafts has a negative effect. or not significant to the welfare of the community in Lubuk Kertang Village. And the results of multiple linear regression testing show the partial hypothesis test results that the value of natural beauty, retribution, tourists and income is significant for the welfare of the people in Lubuk Kertang Village.